(untitled) (Research, Society and Development, 2020)
The objective of the present study was to evaluate the bioremediation of soils artificially contaminated with atrazine, glyphosate and pendimethalin by fungal consortia in biodegradation processes in microcosms. Biodegradation was evaluated from microbial respiration over a period of 15 days and genotoxicity analysis in Allium cepa roots exposed to elutriate samples at zero and 50 μg mL-1 concentrations of the herbicides after the biodegradation process. The results were submitted to analysis of variance, the Tukey test and the Fischer test (p<0.05%) for comparison of means. The Aspergillus fumigatus - Penicillium citrinum consortium had a larger capacity to degrade atrazine but metabolism was inhibited in the presence of glyphosate and pendimethalin. There was a delay in the mitotic index in the meristematic cells of the Allium cepa roots exposed to the elutriates in the 50 μg mL-1 atrazine and pendimethalin concentration. There was a cellular alteration in the metaphase phase of the cells exposed to the elutriates at the 50 μg mL-1 concentration of the three herbicides. The changes occurred were low, indicating that there was degradation of part of the herbicides.